2018
DOI: 10.2478/nbec-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the soybean oil bleaching and optimization of its conditions in the refining process for environmental interest

Abstract: In this work, we propose mathematical models describing the soybean oil bleaching process as a function of its parameters (temperature: 80 – 120 °C, clay dosage: 0.25 – 2 %, contact time: 10 – 30 min). The crude soybean oil visible spectrum shows three values of maximum wavelength (λmax). A value at 426 nm corresponding to the chlorophyll-a, the values at 451 and at 479 nm were assigned to β-carotene pigment. The models were developed using multiple linear regression analysis (MLRA) and were performed with Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…This indicates the release of Al 3+ , Mg 2+ and Fe 3+ cations from the octahedral sheets. The obtained results accord well with those in the previous studies 27–47 and confirm the chemical found analyses.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates the release of Al 3+ , Mg 2+ and Fe 3+ cations from the octahedral sheets. The obtained results accord well with those in the previous studies 27–47 and confirm the chemical found analyses.…”
Section: Resultssupporting
confidence: 92%
“…31 Soybean oil contains colorants, such as chlorophyll, carotenoids and other products whose formulas contain a very large number of double bonds, thus giving the oil a yellowish, reddish color. 32…”
Section: Characterization Of Soybean Oilmentioning
confidence: 99%
“…All the colour values fall within the range of specifications for bleached soybean oil (<5 for red and <50 for yellow [41]) after bleaching with oxalic-acid-activated bentonites. Unlike what occurs with chlorophyll, the removal of colour from the oil does not seem to be dependent on pore diameter.…”
Section: Comparison Of Acid-activated Albe-g and Febe-i Samplessupporting
confidence: 61%
“…The pseudo-second-order kinetic model investigation of the bleaching process can be expressed as following Eq. 5 4,5,28 :…”
Section: Pseudo-second Ordermentioning
confidence: 99%
“…where k 2 (gg −1 min −1 ) is the equilibrium rate constant of pseudo-second-order adsorption 4,28 . The slope of the plot of t/q t versus t was used to determine qe and then from the intercept, k 2 was calculated.…”
Section: Pseudo-second Ordermentioning
confidence: 99%